Muscle pain - Omphile Mogole; Ralph Kandiwa; Oyetola Babarinde; Halima Ismail; Nokuthula Dlamini; Letlhogonolo Maluleke; Quinten Labuschagne; Lucille Malan; Natalie Schellack (South African Family Practice)
Muscle pain, also known as myalgia, is most commonly associated with sprains or strains. It frequently presents as redness at the site of injury, tenderness, swelling and fever. Muscle pain may occur as a result of excitation of the muscle nociceptor due to overuse of the muscle, viral infections or trauma. The most important endogenous substance released in response to the damaged tissues or nociceptor nerve endings in regards with muscle pain is adenosine triphosphate (ATP). Optimal pain management involves a combination of non-opioid, opioid analgesics, adjuvants, as well as non-pharmacologic strategies. Non-opiod analgesics include paracetamol and non-steroidal anti-inflammatory drugs (NSAIDs) like ibuprofen, which are indicated for mild to moderate pain. Whereas moderate to severe pain acquires opiod analgesics. This article provides an overview of muscle pain, the management and treatment thereof.